Effect of endurance training on fatty acid metabolism during whole body exercise - Martin, W. H. (Medicine & Science in Sports & Exercise, 1997)
Endurance exercise training increases fat oxidation during large muscle mass exercise. Although the source of this fat has been thought to be plasma free fatty acids (FFA) released from adipose tissue, the training-induced decrease in lipolytic hormonal responses to exercise is not consistent with this concept. The purpose of this communication was to review findings from the author's laboratory indicating that, in young healthy subjects, endurance exercise training reduces plasma FFA turnover and oxidation during moderate intensity prolonged 2-leg cycling while simultaneously enhancing depletion of triglycerides from active musculature. Evidence is presented that metabolism of intramuscular triglycerides explains the increase in total fat oxidation observed in the trained state during large muscle mass exercise. However, these results may not be applicable to exercise involving small muscle groups, a distinction that is likely to be important in explaining the apparent conflict between the author's findings and those from other laboratories where experimental conditions were different. Implication. The fuel source for large muscle exercise is different to that associated with small muscle activity. This suggests that the fuel for swimming, which mainly uses small muscle groups in the upper body and shoulders, will be different to that of running or cycling, which use large leg and lower abdominal muscles. If this is true, then training programs and expectations for volume and intensity would be dissimilar between sports.